San Pian decoction can treat nitroglycerin-induced migraine in rats by inhibiting the PI3K/AKT and MAPK signaling pathways. (5th October 2022) - Mao, Qiping; Cui, Yushun; Du, Hui; Wu, Jiahui; Zhou, Maofu; Ouyang, Hui; feng, Yuling; Yang, Shiling
Abstract: Ethnopharmacological relevance: San Pian decoction (SPD), a traditional Chinese medicine preparation composed of eight herbs, has been reported to alleviate migraine. However, its active ingredients and the potential mechanism of action remains unclear. The purpose of this study was to comprehensively analyze SPD for the treatment of chronic migraine based on pharmacological direction and to identify the active ingredients and pharmacological mechanism of SPD in the treatment of migraine. Materials and methods: The active components in SPD were identified by AB SCIEX quadrupole time-of-flight mass spectrometer, and the prediction targets and pharmacological networks related to migraine were constructed. The mechanism of SPD in treating migraine was studied through network pharmacology, which was further verified using pharmacological experiments. Results: A total of 489 targets of 26 compounds were identified. Based on Venn analysis, we found 117 intersection targets between SPD and migraine, that is, these targets were related to the treatment of migraine. Gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis revealed that the treatment of migraine using SPD was related to the PI3K/AKT and MAPK signaling pathways. The effect of SPD on migraine was verified by measuring the levels of the inflammatory factors, nitric oxide (NO), interleukin (IL-6), endothelin (ET), 5-hydroxytryptamine(5-HT), indoleamine 2, 3-dioxygenas (IDO), tumor necrosis factor (TNF-α) and calcitonin gene-related peptide (CGRP). Lastly, real-time polymerase chain reaction and western blotting were used to verify gene and protein expression in the PI3K/AKT and MAPK signaling pathways. Expression of the genes P38, JNK, ERK, PI3K and AKT, and the protein expression of p-P38, p-JNK, p-ERK, p-AKT and p-PI3K were significantly downregulated. Our findings indicated that SPD could prevent inflammation by regulating the inflammatory cytokines and key genes and proteins in the PI3K/AKT and MAPK signaling pathways to treat migraine. Conclusion: Our findings reveal that SPD could treat nitroglycerin-induced migraine by regulating p-AKT, p-pI3k, p-p38, p-ERK, p-JNK, IL-6, and TNF-α inflammatory factors in the PI3K/AKT and MAPK signaling pathways. Highlights: Establish migraine model and verify the efficacy of San pian Decoction (SPD). Predict the blood components of SPD prototypes by UPLC-Q/TOF-MS. Network pharmacological studies and molecular docking were conducted on the basis of blood components. verify mitogen-activated protein kinase (MAPK) and PI3K/AKT signaling pathways.